Constrictive pericarditis following inactivated virus COVID-19 vaccine: a case report with review of the literature - Shokoufeh Hajsadeghi, MD; Milad Gholizadeh Mesgarha, MD; Elahe Saberi Shahrbabaki, MD; Maryam Pishgahi, MD; Aria Ebadi Fard Azar, Medical Intern; Arash Pour Mohammad, MD (Radiology Case Reports, 2022)
Cardiac adverse effects of the COVID-19 vaccine are very rare, myocarditis and pericarditis are the most common amid them, and constrictive pericarditis (CP) is reported to be restricted to a few cases following mRNA COVID-19 vaccines. We report a case of a 72-year-old male patient who developed symptoms of right-sided heart failure, which started after 8 days of receiving the third dose of inactivated virus COVID-19 vaccine and his diagnostic tests comprising transthoracic echocardiography, chest CT scan, cardiac magnetic resonance were in favor of CP. Ultimately, invasive cardiac catheterization confirmed the diagnosis of CP. Due to the lack of satisfactory response to corticosteroid therapy, pericardiectomy was performed, which gave rise to symptom relief progressively and substantially. Considering the temporal course of the patient's symptoms and exclusion of other possible etiologies based on the patient's medical history and diagnostic evaluation, immunization with the COVID-19 vaccine was recognized as a culprit for developing CP. Despite being a scarce phenomenon, the COVID-19 vaccine could have a tendency to provoke pericardial inflammation in so far as causing CP. Hence, physicians should have a high index of suspicion in these circumstances and accelerate the diagnostic investigation.